Konstruksi Epistemologi Tafsir Pergerakan Syi’ah - Ade Jamaruddin; Parhulutan Siregar (SUHUF, 2020)
AbstractThe Qur’anic exegetical development is in some ways always related to the background of its production. The relations between the exegete as the author and the text which becomes his or her work is very important to discuss. One of the representative examples of exegetical movement of Shi’a is Muhammad Husain Fadlullah (1935-2010) who is considered to be the spiritual mentor for the Hizbullah movement in Lebanon. The method used in this research is a library research with descriptive, analysis and comparative in its character. The result of this research shows that the Quranic Exegesis cannot stop in the area of linguistic discourse only and its meaning cannot be trapped at the level of linguistic understanding, and that the meaning of the Qur’an should not be limited at the level of logos only. In this regard, Fadlullah calls Muslim community to use of the Qur’an as a source and principle for all movements in everyday life. Key words: Construction, epistemology, Min wahy Al-Qur’an, tafsir Al-Qur’an